An album is a story: Feature arcs in sequences of tracks - Pedro Neto; Martin Hartmann; Geoff Luck; Petri Toiviainen (PLoS ONE, 2025)
When releasing an album, musicians often think about the order in which their songs will be presented to the listener. In a previous study, we analyzed sequencing patterns within a set of 50,000 published works and found that louder, more energetic tracks are usually placed before quieter ones. Here we asked 130 music professionals to deliberately arrange the order of songs for a hypothetical album release. Our findings reveal consistent statistical patterns of track sequencing, with musicians showing broad agreement on the placement of songs within an album. Overall, tempo follows an inverted U-shape, while valence, arousal and loudness exhibit the opposite pattern. Results are interpreted in light of auditory science, and compared with sequencing trends commonly found in song lyrics and literary works.